Method Of Acting Training At The Art Space Foundation In Tuban District - Ilma Akhsanan Nisa'; Welly Suryandoko (PT. Anagata Sembagi Education, 2024)
The training method for an actor is the first step that becomes an important part of the success of a theater performance. The right training for actors is training that can develop their potential, such as the actor training conducted by the Ruang Seni Foundation in Tuban Regency. Actor training conducted by the Ruang Seni Pribumi Foundation is carried out once a year and is attended by high school / junior high school / high school theater communities in Tuban Regency. The research method used is qualitative with a qualitative descriptive approach that uses data collection techniques in the form of direct observation, structured interviews and field documentation in the form of photographs. Researchers used triangulation of sources and techniques to test the validity and truth of the research. The results showed that the Ruang Seni Pribumi Foundation in the acting training conducted absorbed Constanin Stanislavsky's theory of acting from 15 stages into 5 stages to make it easier for trainees to understand the concept of playing a role for an actor. The results of the application of the acting training method can be seen in the performance of actors in portraying characters when participating in festivals and winning, as well as in the best presenter category and the best actor and actress nominations.